2016
DOI: 10.2147/ott.s102265
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vascular endothelial growth factor receptor tyrosine kinase inhibitors in the treatment of advanced thyroid cancer: a meta-analysis of randomized controlled trials

Abstract: BackgroundWe performed a systematic review and meta-analysis to determine the efficacy and safety of the US Food and Drug Administration approved vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKIs) in the treatment of advanced thyroid cancer.Patients and methodsWe included prospective randomized controlled trials that compared VEGFR-TKIs with placebo for advanced thyroid cancer. The endpoints included safety (fatal adverse events [FAEs], treatment discontinuation, and any severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recently, different kinds of novel TKIs have been investigated in cancer patients and shown improving overall survival and progression-free survival. Indeed, two previously published meta-analyses had demonstrated that TKIs treatment in advanced/metastatic thyroid cancer patients was associated with a significantly improved overall survival and progression-free survival, and higher incidence of diarrhea, rash, and hypertension was observed in TKIs treatment group [41, 42]. But the overall incidence and risk of severe ATEs/VTEs associated with TKIs in TCs patients remains undetermined, although these toxicities have been observed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different kinds of novel TKIs have been investigated in cancer patients and shown improving overall survival and progression-free survival. Indeed, two previously published meta-analyses had demonstrated that TKIs treatment in advanced/metastatic thyroid cancer patients was associated with a significantly improved overall survival and progression-free survival, and higher incidence of diarrhea, rash, and hypertension was observed in TKIs treatment group [41, 42]. But the overall incidence and risk of severe ATEs/VTEs associated with TKIs in TCs patients remains undetermined, although these toxicities have been observed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%